KARAKTERISTIK HUTAN MANGROVE DI DESA BOLOBUNGKANG KECAMATAN LOBU KABUPATEN BANGGAI - Kasang, Ariawan M.; Toknok, Bau; Korja, I Nengah (Universitas Tadulako, 2016)
Mangrove forest is one of unique forest ecosystem form which brings land and sea territory. Mangrove forest has specific characters in tidal areas, coastal marine zone and Small Islands in Bolobungkang village, Luwuk-Banggai of Central Sulawesi Province. The study aimed to edetermine Mangrove forest characteristic. Plot is used as the methodology which is placed into aÂ strip with size 10m x 10m for tree level, 5m x 5m for stake level and 2m x 2m for seedling level which set into 20 strip plots along 2 strips. The sampling used is soil sampling which is conducted in aqueous (forward) and in near land area (back). The characteristics of Mangrove forest habitat in Bolobungkang village are loam, sandy loam and dusty loam. The PH ranges 3. 9 â€“ 3. 0 and salinity ranges 2, 73 â€“ 2, 69 per mile. The highest INP for the tree and the stake level is Rhizophora mucronatawith with the value of 116, 86 % and 125, 22 % while the highest of SDR is Rhizophora apiculata with a value of 93, 94 %. Keywords: Mangrove, Forest, Characteristic